Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Cos 3A = Cos ( 2A+ A)

= Cos 2A Cos A - Sin 2A Sin A

= ( 2 Cos²A -1) Cos A - 2 Sin²A Cos A

= 2 Cos³A -Cos A - 2 Cos A( 1- Cos²A)

= 4 Cos³ A- 3 Cos A

HENCE PROVED

= Cos 2A Cos A - Sin 2A Sin A

= ( 2 Cos²A -1) Cos A - 2 Sin²A Cos A

= 2 Cos³A -Cos A - 2 Cos A( 1- Cos²A)

= 4 Cos³ A- 3 Cos A

HENCE PROVED

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Cos 3A = Cos ( 2A+ A)

= Cos 2A Cos A - Sin 2A Sin A

= ( 2 Cos²A -1) Cos A - 2 Sin²A Cos A

= 2 Cos³A -Cos A - 2 Cos A( 1- Cos²A)

= 4 Cos³ A- 3 Cos A

∴ cos 3A= 4 cos³A- 3cosA** **

= Cos 2A Cos A - Sin 2A Sin A

= ( 2 Cos²A -1) Cos A - 2 Sin²A Cos A

= 2 Cos³A -Cos A - 2 Cos A( 1- Cos²A)

= 4 Cos³ A- 3 Cos A

∴ cos 3A= 4 cos³A- 3cosA